PEMBUATAN DAN KARAKTERISASI EDIBLE FILM GALAKTOMANAN DARI BUAH NIPAH (Nypa fruticans Wurmb) DENGAN INKORPORASI EKSTRAK METANOL DAUN TAHONGAI (Kleinhovia hospita L.) SEBAGAI ANTIOKSIDAN - Shintia Alifah R; Subur P. Pasaribu; Erwin Erwin; Aman Sentosa Panggabean (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
Fabrication and characterization of edible films from galactomannan nipah fruit (Nypa fruticans Wurmb) with the incorporation of methanol extract of tahongai leaf (Kleinhovia hospita L.) as an antioxidant has been conducted. This study aims to determine the best concentration of methanol extract of tahongai leaves to increase the antioxidant activity of edible films using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. The results showed that the edible film containing galactomannan 1.5%, glycerol 25% and methanol extract of tahongai leaves with concentrations of 0%, 1%, 2%, 3% and 4% showed antioxidant activity with IC50 values of 224.02 mg/L, 215.82 mg/L, 153.51 mg/L, 129.48 mg/L and 107.87 mg/L respectively. The concentration of incorporation of methanol extract of tahongai leaves to produce the best edible film is 3% which increases antioxidant activity when compared to edible films without incorporation with properties having a moisture content of 15.04%, thickness of 0.21 mm, water vapor transmission of 43.70 g/m2/hour and SEM (Scanning Electron Microscopy) analysis showed the surface morphology was homogeneous and slightly rough. Keywords : Edible film; Galactomannan; Tahongai leaves; Antioxidant activity